Biological Control of Meloidogyne incognita by Spore-forming Plant Growth-promoting Rhizobacteria on Cotton - Xiang, Ni; Lawrence, Kathy S; Kloepper, Joseph W; Donald, Patricia A; McInroy, John A; Lawrence, Gary W (Plant disease, 2017)
In the past decade, increased attention has been placed on biological control of plant-parasitic nematodes using various fungi and bacteria. The objectives of this study were to evaluate the potential of 662 plant growth-promoting rhizobacteria (PGPR) strains for mortality to Meloidogyne incognita J2 in vitro and for nematode management in greenhouse, microplot, and field trials. Results indicated that the mortality of M. incognita J2 by the PGPR strains ranged from 0 to 100% with an average of 39%. Among the PGPR strains examined, 212 of 662 strains (or 33%) caused significantly greater mortality percent of M. incognita J2 than the untreated control. Bacillus was the major genus initiating a greater mortality percentage when compared with the other genera. In subsequent trials, B. velezensis strain Bve2 reduced M. incognita eggs per gram of cotton root in the greenhouse trials at 45 days after planting (DAP) similarly to the commercial standards Abamectin and Clothianidin plus B. firmus I-1582. Bacillus mojavensis strain Bmo3, B. velezensis strain Bve2, B. subtilis subsp. subtilis strain Bsssu3, and the Mixture 2 (Abamectin + Bve2 + B. altitudinis strain Bal13) suppressed M. incognita eggs per gram of root in the microplot at 45 DAP. Bacillus velezensis strains Bve2 and Bve12 also increased seed-cotton yield in the microplot and field trials. Overall, results indicate that B. velezensis strains Bve2 and Bve12, B. mojavensis strain Bmo3, and Mixture 2 have potential to reduce M. incognita population density and to enhance growth of cotton when applied as in-furrow sprays at planting.